Responses to Social Vocalizations in the Dorsal Cochlear Nucleus of Mice - Roberts, Patrick D.; Portfors, Christine V. (Frontiers in Systems Neuroscience, 2015)
Identifying sounds is critical for an animal to make appropriate behavioral responses to environmental stimuli, including vocalizations from conspecifics. Identification of vocalizations may be supported by neuronal selectivity in the auditory pathway. The first place in the ascending auditory pathway where neuronal selectivity to vocalizations has been found is in the inferior colliculus, but very few brainstem nuclei have been evaluated. Here, we tested whether selectivity to vocalizations is present in the dorsal cochlear nucleus (DCN). We recorded extracellular neural responses in the DCN of mice and found that fusiform cells responded in a heterogeneous and selective manner to mouse ultrasonic vocalizations. Most fusiform cells responded to vocalizations that contained spectral energy at much higher frequencies than the characteristic frequencies of the cells. To understand this mismatch of stimulus properties and frequency tuning of the cells, we developed a dynamic, nonlinear model of the cochlea that simulates cochlear distortion products on the basilar membrane. We preprocessed the vocalization stimuli through this model and compared responses to these distorted vocalizations with responses to the original vocalizations. We found that fusiform cells in the DCN respond in a heterogeneous manner to vocalizations, and that these neurons can use distortion products as a mechanism for encoding ultrasonic vocalizations. In addition, the selective neuronal responses were dependent on the presence of inhibitory sidebands that modulated the response depending on the temporal structure of the distortion product. These findings suggest that important processing of complex sounds occurs at a very early stage of central auditory processing and is not strictly a function of the cortex.